2012
DOI: 10.1016/j.jss.2011.11.1003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Fas-Fas Ligand Interaction Attenuates Microvascular Hyperpermeability Following Hemorrhagic Shock

Abstract: Hemorrhagic shock (HS) induced microvascular hyperpermeability poses a serious challenge in the management of trauma patients. Microvascular hyperpermeability occurs mainly due to the disruption of endothelial cell adherens junctions, where the 'intrinsic' apoptotic signaling plays a regulatory role. The purpose of this study was to understand the role of the 'extrinsic' apoptotic signaling molecules, particularly Fas-Fas ligand interaction in microvascular endothelial barrier integrity. Rat lung microvascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Animal studies showed an early increase in endothelial permeability following hemorrhagic shock [14,15], which even further increased following fluid resuscitation [16][17][18]. This was confirmed by a study showing that rodent plasma, collected after fluid resuscitation, induced in vitro rodent endothelial hyperpermeability [19]. However, evidence regarding the effect of human plasma from patients following traumatic hemorrhagic shock on endothelial barrier is limited.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Animal studies showed an early increase in endothelial permeability following hemorrhagic shock [14,15], which even further increased following fluid resuscitation [16][17][18]. This was confirmed by a study showing that rodent plasma, collected after fluid resuscitation, induced in vitro rodent endothelial hyperpermeability [19]. However, evidence regarding the effect of human plasma from patients following traumatic hemorrhagic shock on endothelial barrier is limited.…”
Section: Discussionmentioning
confidence: 97%
“…Current knowledge regarding hemorrhagic shock-induced hyperpermeability is restricted to animal studies [14][15][16][17][18] or in vitro studies investigating the effect of rodent plasma on endothelial barrier function [19]. Animal studies showed an early increase in endothelial permeability following hemorrhagic shock [14,15], which even further increased following fluid resuscitation [16][17][18].…”
Section: Discussionmentioning
confidence: 99%